POLYMER AND CEMENT MORTARS FOR THE CONSTRUCTION AND REPAIR OF BUILDINGS AND STRUCTURE - Pshinko, O. M.; Palii, V. V.; Krasniuk, A. V. (Science and Transport Progress, 2009)
In the article the analysis of polymer-cement mortars for their application in construction and repair of buildings and structures is presented. The main properties of known polymer-cement mortars used for this purpose are described. The advantages of application of polymer-cement mortars as repair materials are shown.